(untitled) (Филолошки студии, 2019)
The paper discusses the relation between the popular culture and croatian drama of the nineties analysing the signs of popular culture in the play John Smith, Princess of Wales by Tomislav Zajec. The focus of the paper is the status of princes Di as a popular icon of the nineties and the concept of queer identity in the play.